MİLLETLERARASI TİCARİ SÖZLEŞMELERDE HUKUK SEÇİMİNE İLİŞKİN LAHEY İLKELERİ VE BU İLKELERİN TÜRKÇE TERCÜMESİ - (:unkn) unknown (My University, 2019)
Belirli bir konuda bağlayıcı nitelik taşımayan ilkelerin yer aldığı metinlerin hazırlanması son yıllarda giderek rağbet gören bir yeknesak-laştırma modeli haline gelmiştir. Bir hükümetlerarası örgüt olan Lahey Milletlerarası Özel Hukuk Konferansı, bu modeli takip ederek Milletle-rarası Ticari Sözleşmelerde Hukuk Seçimine İlişkin İlkeleri 2015 yılında kabul etmiştir. 12 madde ve bir dibaceden oluşan Lahey İlkeleri, adından da anlaşılacağı üzere dar bir alana ilişkindir. Lahey İlkeleri milletlerarası nitelik taşıyan ticari sözleşmelerde hukuk seçimine ilişkin genel esasları belirlemektedir. Bu İlkelerde, sınırlı bazı istisnalar dışında irade serbesti-si esası benimsenmiştir. Lahey İlkeleri, bir konvansiyon veya model kanun değildir. Çalışmamızda öncelikle Lahey İlkeleri’nin hazırlık süre-ci, bu ilkelerin kapsamı ve içeriği açıklanacaktır. Daha sonra Lahey İlke-leri ile MÖHUK’un 24. maddesinin yanı sıra hukuk seçimine ilişkin diğer maddeleri karşılaştırılacaktır. Ayrıca Lahey İlkeleri’nin Türk mah-kemeleri veya Türkiye’de cereyan eden tahkimlerde uygulanması muhtelif olasılıklara göre değerlendirilecektir. Çalışmamızın son kısmında Lahey İlkeleri’ne ilişkin görüş ve önerilerimiz açıklandıktan sonra bu İlkelerin Türkçe tercümesine yer verilecektir.

Drafting non-binding instruments consisting of principles on a particular subject has increasingly become a popular harmonization model in recent years. The Hague International Private Law Conferen-ce, an intergovernmental organization, followed this model and the Principles on Choice of Law in International Commercial Contracts, as its first normative soft-law instrument, developed and approved by the Hague Conference on Private International Law in 2015. The Princip-les, consisting of only twelve articles and a Preamble, are a relatively short document. As their title implies, they refer to a narrow area. The Hague Principles sets forth general principles concerning choice of law in international commercial contracts. They affirm the principle of party autonomy with limited exceptions. The Hague Principles are not a con-vention or model law, but soft law. In this study, the preparation process of the Hague Principles, the scope and content of these principles will firstly be explained. Then the Hague Principles will be compared with Article 24 of the Turkish PILA as well as its other articles dealing with choice of law. Furthermore, the implementation of the Hague Principles by the Turkish courts or in arbitration proceedings conducted in Turkey will be assessed according to various possibilities. In the last part of this study, following the explanations of personal views and suggestions re-garding Hague Principles, the Turkish translation of these Principles will be made.
HAGUE PRINCIPLES ON THE CHOICE OF LAW IN INTERNATIONAL COMMERCIAL CONTRACTS AND TURKISH TRANSLATION OF THESE PRINCIPLES